QUALITY OF ECO ENZYME PRODUCED THROUGH A FERMENTATION PROCESS IN VARIOUS "TEMPE" YEAST CONCENTRATIONS - Dea Resty Novita Maharani; Cucuk Evi Lusiani (DISTILAT: Jurnal Teknologi Separasi, 2023)
Organic waste that accumulates and is not adequately managed causes disease and environmental problems. Therefore, one method to solve the problems is to convert it into eco enzyme, a liquid created from the fermentation of organic waste, specifically vegetable and fruit peels, sugar, and water. Anaerobic fermentation is utilized to produce eco enzymes, with yeast added to shorten the fermentation time. The goal of this research is to determine the effect of "tempe" yeast concentration on the quality of eco enzymes. Eco enzyme was made from brown sugar, fruit peels (oranges and melons), and water in a 1:3:10 ratio. "Tempe" yeast concentrations of 1, 2, 3, 4, and 5 %w/v were used in the fermentation process for producing eco enzyme. The eco enzyme products were examined by analyzing pH value, acetic acid content, Total Dissolved Solids (TDS) value, organoleptic properties (aroma and color), and protease enzyme activity. The pH and TDS values of eco enzyme products increased as the concentration of "tempe" yeast increased. The results showed that eco enzyme products have pH values in the range of 3.5-4, acetic acid content of 0.81-1.08 %v/v, TDS value of 1000-2000 ppm, with fermented and orange aroma and a bright yellow color. According to the results, the addition of 3 %w/v "tempe" yeast in the production of eco enzyme was selected as a sample tested for protease enzyme activity and a clear zone was identified around the colony, indicating that there was protease enzyme activity.